13 Better evidence for better healthcare for all creatures great and small. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Dean, Rachel; Duncan, Jonny; Malone, Jo; Rendle, David; Scobie, Caroline; Shearman, Tim
Abstract : Objectives: The evidence base for the commonly asked questions by veterinary clinicians or animal owners is poor. The research produced by academia and the pharmaceutical industry is often wasted as it can't be applied to practice. VetPartners, one of the fastest growing corporates in the UK, has established a clinical board structure to deliver their clinical excellence strategy. This structure must encompass the challenge of wide geographical distribution and clinical diversity across the network of practices as well as the differences between small animal, equine and production animal settings. It is vital that we deliver high quality evidence-based healthcare to our patients, as a large group of connected healthcare providers we are potentially better placed to do this than independent small practices. Method: A process has been established to ensure common clinical uncertainties are identified from the clinical teams within the business through several routes. Groups of employees with skills, expertise, experience and interest in certain clinical areas have been formed. These groups supported by 3 strategic species-based clinical boards prioritise the uncertainties and develop evidence-based decision-making resources e.g. guidance, protocols, checklists. Where evidence is lacking, the opinion and experience of the clinical workforce are gathered using evidence-based techniques and the ability to undertake our own research is being established. As well as clinically relevant quality improvement cycles we intend to measure the effect of the activities of the vetPartners clinical board on outcomes for our patients, business and clinicians. Results: The challenges to date will be discussed including communication, IT, training, a lack of evidence and how to prioritise the activities in busy clinical and business environments. The benefits of providing this structure is already clear as this group wide activity provides a common purpose for members of staff, improves morale and provides individuals with new opportunities for clinical leadership and developing their EBM skills. Conclusions: The principles behind the EBM manifesto to provide better evidence for better healthcare apply to all clinical settings whatever the species involved. Sharing experiences across the professions provides new opportunities to learn from each other and apply new methods of undertaking evidence-based practice to benefit our patients